Antibiotic Resistance, spa Typing and Clonal Analysis of Methicillin-Resistant Staphylococcus aureus (MRSA) Isolates from Blood of Patients Hospitalized in the Czech Republic - Pomorska, Katarina; Jakubu, Vladislav; Malisova, Lucia; Fridrichova, Marta; Musilek, Martin; Zemlickova, Helena (Antibiotics (Basel, Switzerland), 2021)
Staphylococcus aureus is one of the major causes of bloodstream infections. The aim of our study was to characterize methicillin-resistant Staphylococcus aureus (MRSA) isolates from blood of patients hospitalized in the Czech Republic between 2016 and 2018. All MRSA strains were tested for antibiotic susceptibility, analyzed by spa typing and clustered using a Based Upon Repeat Pattern (BURP) algorithm. The representative isolates of the four most common spa types and representative isolates of all spa clonal complexes were further typed by multilocus sequence typing (MLST) and staphylococcal cassette chromosome mec (SCCmec) typing. The majority of MRSA strains were resistant to ciprofloxacin (94%), erythromycin (95.5%) and clindamycin (95.6%). Among the 618 strains analyzed, 52 different spa types were detected. BURP analysis divided them into six different clusters. The most common spa types were t003, t586, t014 and t002, all belonging to the CC5 (clonal complex). CC5 was the most abundant MLST CC of our study, comprising of 91.7% (n = 565) of spa-typeable isolates. Other CCs present in our study were CC398, CC22, CC8, CC45 and CC97. To our knowledge, this is the biggest nationwide study aimed at typing MRSA blood isolates from the Czech Republic.
Keywords: MRSA; Staphylococcus aureus; clonal analysis; epidemiology; MLST; spa typing; SCCmec typing